2023
DOI: 10.3389/fimmu.2023.1138765
|View full text |Cite
|
Sign up to set email alerts
|

Optimal time for COVID-19 vaccination in rituximab-treated dermatologic patients

Abstract: BackgroundBy depleting circulating B lymphocytes, rituximab time-dependently suppresses coronavirus disease 2019 (COVID-19) vaccines’ humoral immunogenicity for a prolonged period. The optimal time to vaccinate rituximab-exposed immune-mediated dermatologic disease (IMDD) patients is currently unclear.ObjectiveTo estimate the vaccination timeframe that equalized the occurrence of humoral immunogenicity outcomes between rituximab-exposed and rituximab-naïve IMDD patients.MethodsThis retrospective cohort study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
5
4
0
Order By: Relevance
“…In this context, the data on the cellular response to the COVID-19 vaccine in patients with IMIDs treated with rituximab are especially relevant, given the foreseeable negative effect on the humoral response due to its mechanism of action. As expected, a negative association between seroconversion rates to the COVID-19 vaccine and rituximab has been confirmed, identifying the interval between the last RTX infusion and the first vaccination, the number of peripheral B-cells and the immunoglobulin quantity among the related factors [50,51], while the cellular response seems to be preserved [52]. Intervals of 6 to 9 months between the last rituximab administration and COVID-19 vaccination appear to improve the humoral response, although pharmacokinetic studies suggest that the presence of B cells and/or rituximab in the blood predict seroconversion better than time since last infusion [50,51,53].…”
Section: Anti-cd20supporting
confidence: 73%
See 1 more Smart Citation
“…In this context, the data on the cellular response to the COVID-19 vaccine in patients with IMIDs treated with rituximab are especially relevant, given the foreseeable negative effect on the humoral response due to its mechanism of action. As expected, a negative association between seroconversion rates to the COVID-19 vaccine and rituximab has been confirmed, identifying the interval between the last RTX infusion and the first vaccination, the number of peripheral B-cells and the immunoglobulin quantity among the related factors [50,51], while the cellular response seems to be preserved [52]. Intervals of 6 to 9 months between the last rituximab administration and COVID-19 vaccination appear to improve the humoral response, although pharmacokinetic studies suggest that the presence of B cells and/or rituximab in the blood predict seroconversion better than time since last infusion [50,51,53].…”
Section: Anti-cd20supporting
confidence: 73%
“…As expected, a negative association between seroconversion rates to the COVID-19 vaccine and rituximab has been confirmed, identifying the interval between the last RTX infusion and the first vaccination, the number of peripheral B-cells and the immunoglobulin quantity among the related factors [50,51], while the cellular response seems to be preserved [52]. Intervals of 6 to 9 months between the last rituximab administration and COVID-19 vaccination appear to improve the humoral response, although pharmacokinetic studies suggest that the presence of B cells and/or rituximab in the blood predict seroconversion better than time since last infusion [50,51,53]. The evidence points to the special need to individualize the COVID-19 vaccination strategy in patients with IMIDs being treated with rituximab, although it does not seem advisable to delay primary immunization in cases in which it is not advisable to delay treatment due to the activity of the disease [54].…”
Section: Anti-cd20supporting
confidence: 73%
“…An effective strategy for COVID-19 vaccination in immunosuppressed IMDD individuals involves establishing an appropriate interval between immunosuppressant administration and vaccination ( 51 ). Additional doses, including both primary and booster doses of COVID-19 vaccines, are also crucial, as they have the potential to enhance SARS-CoV-2-specific immunity and delay breakthrough COVID-19 infections, respectively ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ACR currently recommends completing the vaccination series approximately 4 weeks prior to the next rituximab dose based on the data on influenza vaccination responses after rituximab [ 27 ]. Additionally, a retrospective cohort study comparing rituximab-exposed and rituximab-naïve patients with immune-mediated dermatologic disease suggested that a nine-month interval between rituximab administration and vaccination optimises immunogenicity while avoiding unnecessary delay in treatment [ 48 ].…”
Section: Biologic Disease Modifying Anti-rheumatic Drugs (Dmards)mentioning
confidence: 99%